ОСОБЕННОСТИ СИСТЕМЫ УПРАВЛЕНИЯ В ОРГАНИЗАЦИЯХ СФЕРЫ ТУРИЗМА - ЕСИМОВА, Д.Д.; Гайнутдинов, Д. (Siberian Journal of Tourism and Economic)
В работе рассмотрены специфика управления в туристской отрасли, приведены основные модели управления в туризме, теоретические модели взаимодействий в рамках оказания туристских услуг. Ключевые слова: туристский продукт, управление в туризме, глобализация в туризме. The article discusses the specifics of management in the tourism industry, the basic models of management in tourism, theoretical models of interactions in the provision of tourism services. Keywords: tourism product, management in tourism, globalization in tourism